2010
DOI: 10.1590/s1679-87592010000400007
|View full text |Cite
|
Sign up to set email alerts
|

Rhodolith bed structure along a depth gradient on the northern coast of bahia state, brazil

Abstract: A B S T R A C TThe aim of this study was to determine the structure of a rhodolith bed along a depth gradient of 5 to 25 m in the shelf in front of Salvador City, a region of northeastern Brazil. The dimensions, morphology and coralline algae composition of the rhodoliths were analyzed, as well as the vitality, density, and associated flora of the bed at three depths: 5, 15 and 25 m. Samples were obtained by SCUBA divers in summer 2007. Five rhodolith-forming taxa were identified: Sporolithon episporum, Lithot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 43 publications
7
44
1
2
Order By: Relevance
“…The characteristics observed in the examined material correspond to those already identified by Foslie (1900b), Taylor (1960), Horta (2000), and Bahia et al (2010) (Table 8). The specimens collected by Horta (2000) occurred between 12 and 22 meters and those collected by Bahia et al (2010) between 5 and 15 meters. The specimens in this study were collected in the midlittoral zone, and between 22 and 25 m in the subtidal zone, thereby expanding the known range of depths at which this species occur.…”
Section: Tomitasupporting
confidence: 86%
See 1 more Smart Citation
“…The characteristics observed in the examined material correspond to those already identified by Foslie (1900b), Taylor (1960), Horta (2000), and Bahia et al (2010) (Table 8). The specimens collected by Horta (2000) occurred between 12 and 22 meters and those collected by Bahia et al (2010) between 5 and 15 meters. The specimens in this study were collected in the midlittoral zone, and between 22 and 25 m in the subtidal zone, thereby expanding the known range of depths at which this species occur.…”
Section: Tomitasupporting
confidence: 86%
“…Keats et al (2000), Harvey et al (2003), Bahia et al (2010), Farias et al (2010), and Basso et al (2011) have set the following criteria for species identification in the genus Lithothamnion: the size of the tetrasporangial conceptacle, the number of cell layers that constitute the roof of tetrasporangial conceptacles, and the presence or absence of depressions around the pores of tetrasporangial conceptacles (Table 7). The presence of this latter characteristic has been considered decisive in identifying specimens of Lithothamnion as L. crispatum.…”
Section: Tomitamentioning
confidence: 99%
“…On the other hand, we observed that largest maerl was linked to deep sites in Brittany (Trevignon, P. calcareum and L. corallioides) and S Portugal (Algarve2, Phymatolithon sp.3). Other authors have reported cases where rhodolith size either increases (Amado-Filho et al 2007, Gagnon et al 2012 or decreases (Steller & Foster 1995, Bahía et al 2010 with depth. However, in our study, the relationship between size and depth is far from clear because other deep sites (San Francisco, Ons) did not follow the pattern and contained small rhodoliths.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the rhodoliths tend to decrease in diameter with increasing depth [39]. All these factors, combined with others still unknown, may affect the richness and abundance of the associated fauna.…”
Section: Discussionmentioning
confidence: 99%